2020
DOI: 10.1021/acs.chemmater.0c02543
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Strain: Controlling the Surface Chemistry of CsPbI3 Nanocrystal Films for Improved Stability against Ambient Reactive Oxygen Species

Abstract: Colloidal halide perovskite nanocrystals (NCs) have the possibility of easy scale-up due to their batch synthesis and have demonstrated excellent optoelectronic properties. In particular, perovskite NCs have remarkably high photoluminescence quantum yields in solution and as thin films and impressive open circuit voltages in photovoltaic devices. Despite these promising results, little work has been done to understand the stability of CsPbI 3 NCs for optoelectronic device applications. It has been previously s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 85 publications
0
44
0
Order By: Relevance
“…[ 169 ] Interestingly, it was found that the commonly used hole transport material Spiro‐OMeTAD could act as an efficient oxygen scavenger to react with the diffused oxygen before initiating the decomposition of the underneath PQD thin films. Thus, the Spiro‐OMeTAD‐encapsulated PQD film can retain 90% of the initial absorptance after 170 h under illumination in ambient conditions (RH 45%), while the control sample showed a fast color decay within 10 h. [ 169 ] Physically, polymer encapsulants such as, poly(ethylene‐ co ‐vinyl acetate) and polydimethyl siloxane can isolate the working areas of PQD devices from external environment, but their high manufacturing cost remains a concern.…”
Section: Photovoltaics and Optoelectronic Applicationsmentioning
confidence: 99%
“…[ 169 ] Interestingly, it was found that the commonly used hole transport material Spiro‐OMeTAD could act as an efficient oxygen scavenger to react with the diffused oxygen before initiating the decomposition of the underneath PQD thin films. Thus, the Spiro‐OMeTAD‐encapsulated PQD film can retain 90% of the initial absorptance after 170 h under illumination in ambient conditions (RH 45%), while the control sample showed a fast color decay within 10 h. [ 169 ] Physically, polymer encapsulants such as, poly(ethylene‐ co ‐vinyl acetate) and polydimethyl siloxane can isolate the working areas of PQD devices from external environment, but their high manufacturing cost remains a concern.…”
Section: Photovoltaics and Optoelectronic Applicationsmentioning
confidence: 99%
“…[145] Luther and coworkers demonstrated that the degradation of CsPbI 3 QDs is 2 orders of magnitude slower than the CsPbI 3 bulk film. [274] In addition, they reported that the compositional instability of CsPbI 3 QDs is dominant, where surface defect states initiate and accelerate the oxidation of QDs to form superoxide and other oxidants. It is well recognized in the community that the complicated structural and phase degradation remains an obstacle for PVK QDs.…”
Section: Degradation Mechanismsmentioning
confidence: 99%
“…Once the superoxide gets access to these vulnerable sites, the structure collapses by propogating chain reactions of the superoxide and ROS. 158 These flaws and surface imperfections can be treated by different strategies for the purpose to achieve long-term stability. 46,54,149 However, the PCE and stability of CsPbI 3 QDs are unacceptable for researchers to compare with counterpart solar cells at the commercial level.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…62,157 It is ascertained from the literature that under coordinated sites of fluctuates device performance and stability. 158,161 Thirdly, the superoxide (O 2 -) can react with CO 2 and 32 produced carbonate (CO 3 2-) and water. Then CO 3 2can produce PbCO 3 and CsCO 3 by reaction with the under coordinated sites of Pb 2+ and Cs + .…”
mentioning
confidence: 99%
See 1 more Smart Citation